2021
DOI: 10.1002/nano.202100050
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine‐functionalized fullerene derivative as an independent electron transport layer enabling efficient and hysteresis‐free regular perovskite solar cells

Abstract: Suitable electron transport materials bearing good interfacial contact, improved electron transport ability, and matched energy levels are indispensable for developing efficient perovskite solar cells (PSCs). Herein, regular (n-i-p) planar Cs 0.05 FA 0.83 MA 0.12 PbI 2.55 Br 0.45 (CsFAMA) PSC devices were fabricated using a pyridine-functionalized fullerene derivative (C 60 -3-BPy) as an independent electron transport layer (ETL), delivering a decent power conversion efficiency (PCE) of 18.22%, which is dramat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Moreover, the strong coordination interactions of C 60 -3-BPy and perovskite lead to an improved film quality of the perovskite film with enlarged grain size and decreased trap state density, consequently contributing to the facilitated electron extraction. [30] Xie et al reported a multiadduct fullerene electron extractor, named hexakis[di(ethoxycarbonyl)methano]-C 60 (HEMC in Figure 1), which was applied as the ETL of inverted PSCs to enhance the photovoltaic performance, including PCEs of 18.93% (champion PCE of 19.53%) in MAPbI 3 -based PSCs, 19.14% (champion PCE of 20. 2%) in the MAPbI x Cl 3-x -based PSCs and 19.21% (champion PCE of 19.98%) in the CsFAMAPbIBr-based PSCs.…”
Section: Coordination Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the strong coordination interactions of C 60 -3-BPy and perovskite lead to an improved film quality of the perovskite film with enlarged grain size and decreased trap state density, consequently contributing to the facilitated electron extraction. [30] Xie et al reported a multiadduct fullerene electron extractor, named hexakis[di(ethoxycarbonyl)methano]-C 60 (HEMC in Figure 1), which was applied as the ETL of inverted PSCs to enhance the photovoltaic performance, including PCEs of 18.93% (champion PCE of 19.53%) in MAPbI 3 -based PSCs, 19.14% (champion PCE of 20. 2%) in the MAPbI x Cl 3-x -based PSCs and 19.21% (champion PCE of 19.98%) in the CsFAMAPbIBr-based PSCs.…”
Section: Coordination Interactionmentioning
confidence: 99%
“…Moreover, the strong coordination interactions of C 60 ‐3‐BPy and perovskite lead to an improved film quality of the perovskite film with enlarged grain size and decreased trap state density, consequently contributing to the facilitated electron extraction. [ 30 ]…”
Section: Functionalized Fullerene Etlsmentioning
confidence: 99%